The Impact of Economics and Financial Literacy in How People Perceive the Effectiveness of the Fiscal Policy of Zimbabwe: Case Study of Harare - Mukwepa, Ngonidzashe (Review of Knowledge Economy, 2020)
This paper investigates the relationship between the perceived Zimbabwean Fiscal Policy (FP) outcomes and the preferences of the people of Zimbabwe, resident in the city of Harare in the context of the Fiscal Policy Framework (FPF) of Zimbabwe. It looks at how people are aware and confident about the FP actions and institutional frameworks in charge of formulating and implementing FP and also how the activities of people complement the FP actions. It looks at the influence of financial and economics literacy on how people understand and respond to FP actions. To make the investigation robust, data was obtained from across different occupations. Governments get elected to a large extent on the basis of their FP. The nature of FP is political on its own. Hence it is important gauge what areas of the FP process need to be adjusted to ensure that the people become positive about those in charge of the FP formulation and implementation together with the FP tools being used. Results obtained from the investigation showed areas where there is rent seeking and time inconsistency showing that serious reforms of the FPF of Zimbabwe are needed to ensure that optimal macroeconomic outcomes are achieved. A serious lack of awareness of the setup of the FP framework of Zimbabwe showed that there must be widespread and effective communication by the authorities on the nature of the FP operations being implemented to ensure that people on the ground complement government efforts to improve the economic performance of Zimbabwe.